The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1439-0418.2012.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leaffolder Cnaphalocrocis medinalis (Guenee) [Lepidoptera: Pyralidae] injury on the plant physiology and yield loss in rice

Abstract: Influence of leaffolder feeding on chlorophyll, PS II activity and plant–water relations, effect of larval density on leaf damage and time course studies on larval feeding behaviour on altered physiological changes in TN1 rice culture were studied. Quantification of yield losses in the field caused by leaffolder was also assessed. Leaffolder damage resulted in 57% reduction in chlorophyll content, 23% reduction in PS II activity and 23% reduction in relative water content in comparison with control. Rice leaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 18 publications
0
25
0
3
Order By: Relevance
“…Pandey (2003) opined that the luxuriant growth of the crop due to higher N application attracts more RLF for shelter and oviposition. Similarly, Padmavathi et al (2013) reported that RLF damage resulted in 57% reduction in chlorophyll. Larval density of more than 3 larvae hill -1 at maximum tillering stage resulted up to 20% unfilled grains and 28-57% reduction in PS II activity.…”
Section: Discussionmentioning
confidence: 99%
“…Pandey (2003) opined that the luxuriant growth of the crop due to higher N application attracts more RLF for shelter and oviposition. Similarly, Padmavathi et al (2013) reported that RLF damage resulted in 57% reduction in chlorophyll. Larval density of more than 3 larvae hill -1 at maximum tillering stage resulted up to 20% unfilled grains and 28-57% reduction in PS II activity.…”
Section: Discussionmentioning
confidence: 99%
“…Rice leafroller C. medinalis is a major pest of rice in many Asian countries (Bautista et al, 1984;Padmavathi et al, 2012). Although control of C. medinalis with chemicals is not difficult (Endo et al, 1987), its occurrence was widespread because many farmers try to reduce the number of insecticide applications as possible due to public concern and the cost of the chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…C. medinalis secara umum dikenal sebagai hama penting pada tanaman padi (Gangwar, 2015). Hama ini merupakan salah satu hama paling merusak pada tanaman padi di Asia (Ahmad, Rehman, Haq, & Mahmood, 2016;Liu, Rao, Li & Li, 2015) dan menurunkan 30-80% hasil panen padi di daerah endemik hama (Nanda & Bisoi, 1990), bahkan pada varietas hibrid dapat mencapai 68-80% (Padmavathi, Katti, Padmakumari, Voleti & Subba Rao, 2013). Ledakan serangan hama C. medinalis sering terjadi di pertanian padi di daerah Asia bagian timur (Liu et al, 2015).…”
Section: Pengendalian Hamaunclassified
“…Banyaknya daun yang rusak menyebabkan proses fotosintesis tanaman menjadi terganggu. Serangan hama ini pada tanaman padi dapat menyebabkan penurunan hasil 63-80% (Padmavathi et al, 2013). Apabila serangan ini terus berlanjut dapat berakibat gagalnya penyediaan bibit karena banyaknya semai yang mati.…”
Section: B Luas Dan Intensitas Serangan Hamaunclassified